Are Plant-Based Diets Detrimental to Muscular Strength? A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Miguel López-Moreno; Eugenio Viviani Rossi; José Francisco López-Gil; Paula Marrero-Fernández; Alberto Roldán-Ruiz; Gabriele Bertotti (Sports Medicine - Open)
Abstract Background The increasing interest in plant-based diets (PBDs) results from their beneficial impact on human health and environmental sustainability. However, the effect of PBDs on muscular strength in athletes remains unclear. This systematic review and meta-analysis evaluated the impact of PBDs on muscular strength compared to omnivorous diets in adult populations. Methods The methodology was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a comprehensive and transparent review process. Four electronic databases—MEDLINE, The Cochrane Library, Web of Science, and Scopus—were searched from their inception to September 2, 2024. Randomized controlled trials (RCTs) that evaluated the impact of PBDs on the lower body, upper body, and overall muscular strength were included. The risk of bias for the included RCTs was assessed using the Cochrane Risk of Bias 2.0 tool. Standardized mean differences (SMD) were used to estimate effect sizes, and multiple random-effects meta-analyses were conducted using an inverse variance model with Paule-Mandel adjustment. Results Eight RCTs met the inclusion criteria, involving a total of 188 participants (46% women; mean age between 20 and 65 years). The meta-analysis indicated that there were no significant differences between PBDs and omnivorous diets in terms of upper body muscular strength (SMD, − 0.12; 95% confidence interval [CI], − 0.50 to 0.27; n = 146), lower body muscular strength (SMD, 0.18; 95% CI, − 0.31 to 0.67; n = 188), and overall muscular strength (SMD, 0.21; 95% CI, − 0.16 to 0.58; n = 188). Conclusions This meta-analysis suggests that PBDs do not compromise muscular strength compared to omnivorous diets. Further investigation considering key nutrients is necessary to ascertain the long-term effects of these dietary patterns on strength outcomes.